Mating behaviour and female mate choice in the Harvest mouse (Micromys minutus) - Brandt, R (2010)
The harvest mouse (Micromys minutus) is Britain’s smallest rodent, and one of its least‐studied mammals. Mounting concerns over the status of its British populations highlights the paucity of information about this species, not least about different aspects of its behaviour. I study the mating behaviour of the harvest mouse, focusing on female mate choice, and specifically on the effect familiarity with the male has on the female’s mating preference. In order to isolate the role of familiarity on female mate choice, I conducted a controlled choice experiment, in which the female had a choice between two tethered males ‐ one familiar and one unfamiliar to her. The results support the prediction that female harvest mice prefer familiar males over unfamiliar ones when they are in oestrus. Results also reveal that females spend more time in proximity to unfamiliar males when they are not in oestrus, and that the difference in the body weight of the males affects the strength of their response. A more naturalistic experiment was also set up, in which a female and two males ‐ again one familiar and one unfamiliar – were allowed to interact unhindered. This setup allowed the recording of full mating cycles, including copulations. These experiments provide descriptive information about both inter‐ and intra‐sexual interactions surrounding mating. Dominance relations between the two males were very clear cut and the female mated with the dominant male, and only with him. Familiarity did not seem to affect the female’s mating preference. In summary this study shows that female harvest mice prefer familiar males over unfamiliar ones and that male familiarity and dominance interact to influence female mate choice. The study also provides background information about the harvest mouse’s mating behaviour and intra‐male interactions with potential significance for the understanding of other aspects of the natural history of this poorly studied species.